Locus of Control Remaja dalam Perspektif Gender di Lembaga Pendidikan Islam - Sugeng (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2019)
The purpose of this study was to find out an overview of: 1) locus of control in general 2) Differences in locus of control between adolescent boys and girls in adolescents MTs Al-Hikmah Proto Kedungwuni Pekalongan; and 3) Analysis of adolescent locus of control in a gender perspective. The results showed that locus of control is one of the individual personality variables regarding the belief in self-control of events experienced in a self-determined life (internal locus of control) or controlled by an external environment (external locus of control). Field data on adolescent MTs al-Hikmah Proto Kedungwuni Pekalongan shows that both men and women obtained results that their Internal Locus of Control is higher than external Locus of Control. Based on the results that have been obtained, that there is no significant difference in scores between locus of control between male and female students at MTs Al-Hikmah Proto Pekalongan. Therefore parallels between men and women should be considered in all matters of duties and responsibilities, both in education and daily life and society.